Social Capital and the Performance of the Small, Medium and Micro Enterprises in Eastern Cape Province of South Africa - Klaas, Anesipho; Chimucheka, Tendai (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
The small, medium and micro enterprises (SMMEs) are essential drivers to the social and economic growth. These enterprises have an essential role in employment creation and eradication of poverty in South Africa. SMMEs in South Africa are comprised of heterogeneous groups of businesses in various sectors including services, manufacturing and agriculture. This study investigated the effect of social capital on the performance of SMMEs. Thus, the primary objective of the study was to investigate the effect of social capital on the performance of SMMEs in Makana Municipality, and the secondary objectives were to determine the effect of bonding social capital on the performance of SMMEs and to determine the effect of bridging social capital on the performance of SMMEs. Purposive sampling was used to select the respondents. In order to collect data, the researchers distributed 126 questionnaires to SMME owners and managers in the towns within the Makana Municipality. It was found that all the forms of social capital have a positive effect on the performance of SMMEs.